1984
DOI: 10.1016/0014-5793(84)80577-3
|View full text |Cite
|
Sign up to set email alerts
|

Increase of proton electrochemical potential and ATP synthesis in rat liver mitochondria irradiated in vitro by helium‐neon laser

Abstract: not received MitochondriaLaser Transmembrane proton gradient Membrane potential A TP synthesis Oxygen uptake

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
220
0
19

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(260 citation statements)
references
References 10 publications
15
220
0
19
Order By: Relevance
“…Our previous study, in line with others, have shown that LLL illumination can sustain mitochondrial functions in cells under various conditions of stress, including enhancement of ATP synthesis, suppression of ROS production, and reduction of apoptosis. [26][27][28] The ability of sustaining mitochondrial functions in the injured brain may account for the benefit of LLL in TBI management showed recently. 12,17,28 The current investigations further validate that LLL stimulates ATP production and suppresses ROS generation in hypoxic cells and brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study, in line with others, have shown that LLL illumination can sustain mitochondrial functions in cells under various conditions of stress, including enhancement of ATP synthesis, suppression of ROS production, and reduction of apoptosis. [26][27][28] The ability of sustaining mitochondrial functions in the injured brain may account for the benefit of LLL in TBI management showed recently. 12,17,28 The current investigations further validate that LLL stimulates ATP production and suppresses ROS generation in hypoxic cells and brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] This absorbed energy is transformed into ATP that increases the activity of the mitochondrial proton pump, increasing oxygen consumption and enhancing synthesis of nicotinamide adenine dinucleotide dehydrogenase (NADH), RNA and protein. [12][13][14] Finally, these changes will lead to increased expression of growth factors and cell proliferation. 18,19 Furthermore, the most important intracellular organelle that produces reactive oxygen species (ROS) is the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Karu [4] reported several years ago that light therapy effects on biological tissues can be classified as either primary (light-tissue interactions) or secondary mechanisms (photobiomodulation). One of the most frequently observed effects of photobiomodulation is the increased ATP synthesis in cultured cells [4,13,14].…”
Section: Introductionmentioning
confidence: 99%